Acute Traumatic and Ischemic Spinal Cord Injuries Have a Comparable Course of Recovery. (August 2020) - Scivoletto, Giorgio; Torre, Monica; Mammone, Alessia; Maier, Doris D.; Weidner, Norbert; Schubert, Martin; Rupp, Ruediger; Abel, Rainer; Yorck-Bernhard, Kalke; Jiri, Kriz; Curt, Armin; Molinari, Marco
Background . The relative rarity of ischemic compared with traumatic spinal cord injury (SCI) has limited a comparison of the outcomes of these conditions. Objective . To investigate the neurological and functional recovery of ischemic compared with traumatic acute SCI. Methods . Data were derived from the European Multicenter Study Spinal Cord Injury database. Patients with ischemic (iSCI) or traumatic SCI (tSCI), aged 18 years or older were evaluated at different time points from incidence: at about 1 month, 3 months, and 6 months. The neurological status was assessed at each time point by the International Standards for Neurological Classification of Spinal Cord Injury and the functional status by the Spinal Cord Independence Measure. Walking ability was evaluated by Walking Index for Spinal Cord Injury, 10-Meter Walk Test, and 6-Minute Walk Test. Because of the imbalances of the 2 groups in respect to size and lesion severity, a matching procedure according to age, neurological level, and severity of injury was performed. Outcomes evaluation was performed by means of a 2-way repeated-measures ANOVA. Results . The matching procedure resulted in 191 pairs. Both groups significantly improved from about 15 days after the lesion to 6 months. No differences were found in the course of neurological and functional recovery of iSCI compared with tSCI. Conclusions . This analysis from a representative cohort of participants revealed that from 15 days following the cord damage onward, the outcomes after iSCI and tSCI are comparable. This finding supports the potential enrolment of patients with acute iSCI into clinical trials from that point in time after the event and an evaluation up to 6 months afterward.